Is Amanita phalloides Nephrotoxicity due to Mitochondrial Toxicity? - Jules Weinhard; Justine Serre; Perrine Frère; Clovis Adam; Marie Camille Lafargue; David Buob; Cédric Rafat (Kidney Medicine)
Amanita phalloides-related kidney toxicity is poorly documented and remains to be elucidated. Herein, we describe the case of a 43-year old patient who presented with severe liver failure following the ingestion of Amanita phalloides. Although liver injury subsided following the administration of N-acetyl cystein and silibinin, the patient subsequently developed KDIGO stage 3 acute kidney injury. Histopathological examination of the kidney displayed moderate tubular injury characterized by dilated tubular lumens and flattening of the tubular epithelium on optic microscopy. Electron microscopy showed mitochondrial changes including swelling and decreased number of cristae. Immunofluorescence for the key mitochondrial protein TOM20 found significantly decreased expression compared with ischemic acute tubular injury. Despite these changes, histoenzymology showed preserved succinate cytochrome c oxidase (COX) expression, suggesting that mitochondrial complex IV function was maintained. Our findings suggest that Amanita phalloides elicits acute tubular injury via mitochondrial damage, possibly through a pathway that spares COX function. Plain-Language Summary: Kidney damage caused by Amanita phalloides (death cap mushroom) is not well understood. We report the case of a 43-year-old patient who experienced severe liver failure after eating this mushroom. While treatment with N-acetyl cysteine and silibinin improved the liver damage, the patient later developed severe kidney injury. Tests on the kidney showed damage to its tubules inside, with changes in their structure under a microscope. Closer examination revealed that the energy-producing parts of the cells, called mitochondria, were swollen and had fewer folds (cristae), which are essential for energy production. However, one key mitochondrial function, involving an enzyme called complex IV, appeared to be unaffected.This case suggests that the death cap mushroom may harm kidneys by damaging mitochondria in a way that leaves certain functions intact.